Horace Callaway Carlisle poems - Carlisle, Horace Callaway, 1871-
Chiefly typescripts of unpublished poems by Carlisle. Includes "After-Glow from the Overflow," "Besetting Sins," "Crystals from the Cross," "Declining Age's Final Pages," "From My Birth Up," "Golden Rule Melodies," "Library of Congress," "Manual to Memorial to America," "Meditations of Uncle Mose," "Memorial to America," "Our Presidents," "Parodies of Praise," "The United States in a Benighted World," "The Way, the Truth, the Life," and "Whither Bound?"
Author, poet, and teacher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Library of Congress -- Poetry; American poetry; Authors; Educators; Poets